Analisis Pergerakan Harga Emas Berjangka Menggunakan Model Fuzzy Time Series Markov Chain - Afrimayani Afrimayani; Darvi Mailisa Putri (UIN Imam Bonjol Padang, 2023)
Gold is one type of precious metal that can be an investment instrument to protect the value of wealth. Gold price movements need to be known in investing, this can be observed usinga time series model that can predict gold prices in the next period. Gold price movement models can be used as investor guidelines in planning and decision making to increase profits and prevent losses. Gold price movements modeled with a numerical approach can be done through the Fuzzy Time Series Markov Chain (FTSMC) model. The modeling results show that the FTSMC can model gold prices and has good accuracy values with small MAPE, RMSE, and MAE values. This indicates an excellent goodness of fit for the FTSMC model. Long-term stability for gold price movements provides investment benefits because gold has value as an asset that tends to be stable, easy to liquidate in cash, free from interest, has a role as an emergency fund and can protect the value of wealth.